Spatial and Ontogenetic Patterns in the Trophic Ecology of Juvenile Bull Sharks (Carcharhinus leucas) From the Northwest Gulf of Mexico - TinHan, Thomas C.; Wells, R. J. David (Frontiers in Marine Science, 2021)
A combination of stomach content and stable isotope (δ13C, δ15N, and δ34S) analyses were used to characterize and examine spatiotemporal and ontogenetic trends in the feeding ecology of juvenile bull sharks (Carcharhinus leucas) captured in estuaries throughout the northwest Gulf of Mexico (GoM) between 2013 and 2016. Shark diets were dominated by fish prey taxa [>98% index of relative importance (%IRI)], and of those identified to the family level, two families comprised greater than 50% IRI, Mugilidae (mullets: ∼32%) and Sciaenidae (drums and croakers: 27%). Clupeidae (herrings: 14%) and Ariidae (sea catfishes: 15%) also contributed substantially to the diet of juvenile sharks, though consumption of Ariidae increased as consumption of Clupeidae decreased in juvenile sharks larger than 893 mm Fork Length (FL) (∼1 year old). Values of δ15N increased significantly with shark size, indicating a shift toward larger or higher trophic level prey with increasing shark size. Latitudinal and temporal trends in δ13C and δ34S suggest isotopic variation occurred in correspondence with shifts in primary producer assemblages and environmental drivers of sampled estuaries. These results highlight the importance of teleost prey resources along the freshwater-marine continuum in the diet of juvenile bull sharks, as well as the utility of natural tracers in tracking ontogenetic trends in feeding ecology.